(3x^2 - 2x)(x + 4)
<em><u>First step would be: distributive property.</u></em>
3x^3 + 12x^2 - 2x^2 - 8x
<em><u>Combine like terms.</u></em>
3x^3 + 10x^2 - 8x is the simplified form of the functions multiplied.
Your answer is D.
Answer:
Step-by-step explanation:
The equation for cosine is <span><span><span>cos<span>(x)</span></span>=<span>Adjacent/Hypotenuse
</span></span></span>The inside trig function is <span><span>arccos<span>(<span>3/5</span>)</span></span></span>, which means <span><span><span>cos<span>(x)</span></span>=<span>3/5</span></span></span>. Comparing <span><span><span>cos<span>(x)</span></span>=<span>Adjacent/Hypotenuse</span></span></span> with <span><span><span>cos<span>(x)</span></span>=<span>3/5
</span></span></span>
Find <span><span>Adjacent=3</span></span> and <span><span>Hypotenuse=5.
</span></span>Then, using the Pythagorean theorem, find <span><span>Opposite=?
</span></span>a² = c² - b²
a² = 5² - 3² = 25 - 9 = 16
a = √16 = 4
<span><span>Adjacent=3</span></span><span><span>Opposite=4</span></span><span><span>Hypotenuse=5
</span></span><span>
Plug in the value for sin(x) = opposite/hypotenuse
sin(x) = 4/5 </span>
You have -3y=-2x+6 divide both sides by -3 and you'll get:<span><span><span>−3y</span><span>−3</span></span>=<span><span>−2x</span><span>−3</span></span>−<span>63
</span></span>its y=2/3x-2